2002
DOI: 10.1038/nature00954
|View full text |Cite
|
Sign up to set email alerts
|

The ELF4 gene controls circadian rhythms and flowering time in Arabidopsis thaliana

Abstract: Many plants use day length as an environmental cue to ensure proper timing of the switch from vegetative to reproductive growth. Day-length sensing involves an interaction between the relative length of day and night, and endogenous rhythms that are controlled by the plant circadian clock. Thus, plants with defects in circadian regulation cannot properly regulate the timing of the floral transition. Here we describe the gene EARLY FLOWERING 4 (ELF4), which is involved in photoperiod perception and circadian re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

33
491
2
2

Year Published

2005
2005
2007
2007

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 429 publications
(534 citation statements)
references
References 23 publications
33
491
2
2
Order By: Relevance
“…It was noted that, after transfer to constant conditions following exposure to LD cycles, elf4-1 mutant plants displayed weak rhythmicity on the first day (Doyle et al, 2002). This could mean that the oscillator was, upon transfer to constant conditions, running down rather than stopping instantly.…”
Section: Elf4-1 Mutants Arrest Their Clock In the Eveningmentioning
confidence: 99%
See 4 more Smart Citations
“…It was noted that, after transfer to constant conditions following exposure to LD cycles, elf4-1 mutant plants displayed weak rhythmicity on the first day (Doyle et al, 2002). This could mean that the oscillator was, upon transfer to constant conditions, running down rather than stopping instantly.…”
Section: Elf4-1 Mutants Arrest Their Clock In the Eveningmentioning
confidence: 99%
“…We have shown previously that ELF4 is expressed in the evening and that the elf4 loss-of-function mutant has low CCA1 expression leading to arrest of the elf4 oscillator after one cycle under free run (Doyle et al, 2002). Recently, it was shown that elf4 also has low LHY transcript levels, implicating ELF4 in a feedback loop with CCA1 and LHY (Kikis et al, 2005).…”
mentioning
confidence: 99%
See 3 more Smart Citations